Application of laser heating and its effects on bonding strengths for varied copper wire purity levels - Singh, Gurbinder; Haseeb, A.S. Md. Abdul (Laser Institute of America, 2018)
Gold as the medium of interconnection is rapidly being replaced by copper as a means of creating connectivity in integrated circuit packaging. However, the use of copper wire is known to pose many threats in integrated circuit packaging, especially for devices with very thin die structures. The process of wire bonding which involves the formation of free air ball can be risky to the quality of integrated circuit packaging. The impact of hard copper free air ball onto the bonding surfaces may damage the bond pad and the silicon die. These challenges require innovative solutions that are able to be applied to integrated circuit packaging with minimal thermal and mechanical effect on the device. Through recent research, it is apparent that the laser processing technology can provide viable innovative solutions to electronic packaging. This research paper investigates the application of laser heating on copper wire bonding technology and its effects on bonding strength for three copper wire purity types, 99.9% purity (3 N), 99.99% purity (4 N), and 99.999% purity (5 N) copper wires. Wire bonding was performed on bond pads consisting of NiPdAu metallization under 16 different temperature conditions. Results of this study showed that different copper purity levels exhibit different bonding strengths with the application of laser heating. It is shown in this research that significantly higher as-bonded ball shear strengths were obtained when laser heating was applied at all three copper wire purity types. The results of this study can be helpful for integrated circuit packaging with copper wire bonding on thin die structures. Copper wires with lower purity levels are shown as a viable option by further improving the wire bonding quality with the application of laser heating without the need to use excessive bonding temperature, higher bonding force, and excessive ultrasonic energy.